2021
DOI: 10.1155/2021/3482879
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity Differences in the Association of UCP1-3826A/G, UCP2-866G/A and Ala55Val, and UCP3-55C/T Polymorphisms with Type 2 Diabetes Mellitus Susceptibility: An Updated Meta-Analysis

Abstract: Background. The relationship between uncoupling protein (UCP) 1-3 polymorphisms and susceptibility to type 2 diabetes mellitus (T2DM) has been extensively studied, while conclusions remain contradictory. Thus, we performed this meta-analysis to elucidate whether the UCP1-3826A/G, UCP2-866G/A, Ala55Val, and UCP3-55C/T polymorphisms are associated with T2DM. Methods. Eligible studies were searched from PubMed, Cochrane Library, and Web of Science database before 12 July 2020. Pooled odds ratios (ORs) with corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…UCP-encoding gene is located on human chromosome 11. [23][24][25] Studies have revealed that UCP2 polymorphism may play a pathological role in diabetes and cancer. [26][27][28] Other studies have found a negative correlation between UCP2 and glucose-stimulated insulin secretion; UCP2 upregulation inhibits insulin secretion and increases the risk of type 2 diabetes.…”
Section: The Underlying Mechanisms Of Diabetes and Thyroid Cancer Her...mentioning
confidence: 99%
“…UCP-encoding gene is located on human chromosome 11. [23][24][25] Studies have revealed that UCP2 polymorphism may play a pathological role in diabetes and cancer. [26][27][28] Other studies have found a negative correlation between UCP2 and glucose-stimulated insulin secretion; UCP2 upregulation inhibits insulin secretion and increases the risk of type 2 diabetes.…”
Section: The Underlying Mechanisms Of Diabetes and Thyroid Cancer Her...mentioning
confidence: 99%